Frequency of Functional Constipation in Lebanese Children: A Cross-Sectional Study Based on Parental Reporting - Theresia Tannoury; Jana Assy; Nadine Yazbeck (Hindawi Limited, 2024)
Conclusion: The present study shows that 32.6% of children aged 2-7 years in Lebanon suffer from constipation while only 51.7% of the recruited children's physicians inquire about the child's bowel movement during the well check visit. These numbers highlight the need to raise more awareness among pediatricians on the need to screen for constipation during clinic visits as a standard of care practice.